Azithromycin improves lung function in patients with post‐lung transplant bronchiolitis obliterans syndrome: a meta‐analysis. (9th July 2014) - Kingah, Pascal L.; Muma, Gilbert; Soubani, Ayman
Abstract Introduction Azithromycin has been shown to reverse or halt the decline of forced expiratory volume in one s (FEV1) in patients with bronchiolitis obliterans (BOS) syndrome following lung transplant. The overall effect of azithromycin on the absolute values of FEV1 has not been compared between reported studies. We studied the effects of azithromycin on lung function in patients with post‐lung transplant BOS syndrome. Methods A meta‐analysis was performed using studies identified following an extensive database search. To be included, studies were published in English or French and explicitly reported percentage change in FEV1 or hazard ratios. Results A total of 10 studies were included in this review. One hundred and forty patients were evaluated after treatment with azithromycin for an average follow‐up period of seven months. The mean percentage increase in FEV1 was 8.8 (CI 5.1–12.47) p < 0.001. The pooled hazard ratio was 0.25 (CI 0.06–0.56) p = 0.041 for a mean follow‐up period of 2.9 yr. Conclusion This study demonstrated a significant improvement in lung function in patients with BOS syndrome following lung transplant after seven months of treatment. It remains uncertain whether this improvement stays after seven months. We also found that patients on azithromycin were less likely to die from BOS syndrome compared with patients who were not on azithromycin.